Reliability of measures of quadriceps muscle function using magnetic stimulation. Issue 5 (28th March 2016) - Tofari, Paul J.; Opar, David A.; Kemp, Justin G.; Billaut, Francois; Cormack, Stuart
ABSTRACT: Introduction : Magnetic stimulation can be used to assess muscle function by calculating voluntary activation using an interpolated twitch during maximal voluntary contractions (MVCs) and control twitches to potentiated muscle. In this study we assessed the reliability of torque, electromyography (EMG), and voluntary activation variables. Methods : Fifteen men completed 5 testing sessions (2 familiarization and 3 reliability trials) to assess quadriceps femoris muscle function. Intra‐ and interday reliability levels of torque and EMG variables were estimated using typical error ± 90% confidence limits, expressed as percentage [coefficient of variation (CV)] and intraclass correlation coefficient. The smallest worthwhile change was calculated as 0.2 × between‐participant standard deviation. Results : Intra‐ and interday torque variables for MVC were reliable (CV < 4%, ICC 0.98, and CV < 5%, ICC 0.99, respectively). EMG variables were less reliable than torque variables, with CVs ranging from 7% to 18%. Conclusion : Magnetic stimulation of the femoral nerve is a reliable method for assessing muscle function. Muscle Nerve 53 : 770–778, 2016